Update on the Law Regarding the Control of Minimarket to Protect Small Retailers - Indrajaya, Indrajaya; Tanzili, Mulyadi (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
The increase in the establishment of minimarkets has implications for micro and small business actors, including owners of grocery stores and stalls that sell goods similar to minimarkets. Whereas this business sector is the largest in contributing to the Indonesian national economy. One of the factors causing the increase in the establishment of minimarkets is the regulation made by the government in the form of laws, government regulations, presidential regulations and ministerial regulations that provide convenience in the establishment of minimarkets. Therefore, it is necessary to have legal arrangements in regulating the increase in the establishment of minimarkets in order to protect micro and small businesses. This Journal writing uses normative legal research methods using primary legal materials and secondary data obtained through library data. The results showed that there was an impact of the existence of minimarket outlets on the income of retail traders and grocery stores experiencing changes in income. the traders experienced a decrease in turnover and the amount of income per day. The implication becomes the basis for the formation of the concept of new rules in maintaining business balance as an effort to protect the business actors of Grocery Stores and Stalls from the rampant establishment of Minimarket in the form of a review of the articles related to the existence of Minimarket adjacent to residential areas and fill the legal vacuum related to the distance setting of Minimarket establishment with other Minimarket as well as restrictions on granting business licenses, setting working hours and setting administrative sanctions.